Uji Validitas dan Reliabilitas dalam Edukasi Agama Islam untuk Anak Usia Dini melalui Film Rara dan Nussa di Era Digital dengan Software SPSS - Aryanti, Friska; Wahyono, Qhintara F. P.; Jannah, Lusia K.; Araminta, Calyca D.; Kusumastuti, Erwin (SM Institute, 2024)
In the rapidly evolving era of technology, the need for innovative and effective Islamic education for young children is becoming increasingly pressing. Therefore, this research aims to explore the effectiveness of the film